Paralinguistic Features in Students’ Speaking Performance - Meta Idayanti Girsang; Desri Maria Sumbayak; Muhammad Yusuf (Talenta Publisher, 2021)
Analyzing paralanguage in students’ speaking is important especially in the EFL ( English as a Foreign Language) context. The research aims to find out the students’ productions of the paralinguistic features that is pitch and intonation in their speaking performance. The researcher used qualitative research and the data were taken from the eight videos of the speaking project of the students of the English department, Universitas Sumatera Utara.The interpretation of the data showed that each student uses the same feature in their speakings but produced the feature in a different way. The research revealed by seeing their paralinguistic features productions by using an instrument, PRAAT. The researcher found that some students produced low pitches in their speaking and some are high. There was a significant difference between men and women speakers in producing pitch. The research showed that PRAAT can help to reveal that both the students and the lecturer of speaking need to give more attention to the paralinguistic features and the production to build a good speaking and to be able to produce and follow the norms and rules in language they are learning.